Fabrication of strain sensor based on silver conductive ink - Sabri, Zufarina Aqila Lukman (Universiti Sains Malaysia, 2017)
The strain sensor is an essential part of a smart system. In this research, a strain sensor is being prepared by using polydimethylsiloxane (PDMS) as substrate and silver filler as a conductive ink. The ingredients used for substrate preparation are polydimethylsiloxane-hydroxide (PDMS-OH), fumed silica, toluene, dibutyltin dilaurate and 3-glycidoxypropyl-3 trimethoxysilane. The silver conductive ink was printed by stencil printing on the PDMS substrate. Various testing has been conducted to investigate the electrical properties of the strain sensor sample. The strain sensor showed increasing resistance as the applied strain increased. The electrical resistance of the strain sensor also increased day by day. Besides, the strain sensor showed good consistency in resistance at constant strain for 4 hours. Moreover, the properties of the substrate and conductive ink of the strain sensor also are being identified by FTIR, TGA, DSC, SEM and tensile testing. There is no OH bond presence from FTIR result, indicated that the sample was fully cured. PDMS substrate has high tensile strength and elongation at break which means that it is suitable to be used as a substrate